Revision of the genus Doratura Sahlberg (Hemiptera, Cicadellidae, Deltocephalinae) with particular regard to its distribution in Italy and description of four new species - Bückle, Christoph; Guglielmino, Adalgisa (Zootaxa, 2022)
The genus Doratura is revised. Twenty-three valid species are discriminated including four new species: D. lobele sp. nov., D. jole sp. nov., D. roesle sp. nov., and D. vefele sp. nov. The following five species are treated as new synonyms: D. ivanovi Kusnezov, 1928 syn. nov. of D. impudica Horváth, 1897, D. veneta Dlabola, 1959 syn. nov. of D. paludosa Melichar, 1897, D. astrachanica Vilbaste, 1961 syn. nov. of D. rusaevi Kusnezov, 1928, D. littoralis Kuntze, 1937 syn. nov. of D. homophyla (Flor, 1861), and D. arenicola Logvinenko, 1975 syn. nov. of D. caucasica Melichar, 1913. D. paludosa is redescribed. For each species, its habitus and genital morphology are illustrated, a short diagnosis is given, its distribution is outlined and distribution maps are added. If available, data on ecology and phenology are furnished. The Doratura species are distributed in six groups with the exception of D. salina Horváth, 1903, D. horvathi W. Wagner, 1939, and D. lobele sp. nov. For males, an identification key to all Doratura taxa is presented. For females, a preliminary key is proposed. Some other Chiasmini genera are examined in order to suggest possible apomorphic characters in the genus Doratura. Relationships among the Doratura species and the different species groups, distribution patterns, possible hybrids, dispersal strategies in the context of brachyptery, and intraspecific variability in adults and nymphs are discussed.